The Brazilian economic authorities’ action during the covid-19 crisis and an empirical analysis of the fiscal and monetary policies in the period 1996-2020 - Araujo, Elisangela Luzia; Araújo, Eliane; Ferrari Filho, Fernando (Brazilian Keynesian Review, 2022)
This article analyses the countercyclical economic policies, in particular the fiscal and monetary ones, implemented by the Brazilian Economic Authorities (BEAs) in response to the COVID-19 crisis of 2020, as well as it presents an empirical analysis of these economic policies during the period 1996-2020. The main objective is to evaluate the effectiveness of those policies in economic contexts of growth and crisis to aim at showing that countercyclical Keynesian economic policies matter. The empirical part of the article analyzes the effects of fiscal (government spending) and monetary (interest rate) policies on the Brazilian economy during the period 1996-2020. Thus, it is estimated a MS-VAR model to analyze the impact of these economic policies in periods of economic growth and economic crisis. The main results indicate that the effects of fiscal and monetary policies are more pronounced in situations of economic crises than in contexts of economic growths, supporting, thus, the Idea that countercyclical fiscal and monetary policies are able to affect the economic cycles, mainly in periods of crises, as emphasized by Keynes.